2013
DOI: 10.3892/ijo.2013.1990
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic identification of keratin alterations with enhanced proliferation of oral carcinoma cells by loss of mucosa-associated lymphoid tissue 1 expression

Abstract: Progression of oral carcinomas associates with aberrant activation and inactivation of molecules that work in established or unknown pathways. Although mucosa‑associated lymphoid tissue 1 (MALT1) expressed in normal oral epithelium is inactivated in the aggressive subset of carcinomas with worse prognosis, phenotypic changes of carcinoma cells upon the loss of expression is unknown. We performed a proteomic analysis to identify MALT1‑regulated proteins in oral carcinoma cells. Four different keratins were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…The wtMALT1 HSC2 cells decelerated proliferation compared to mock HSC2 cells, and it was supported by the slow proliferation of endogenous MALT1-positive cells. This is consistent with cyclin D1 expression, which is almost terminated in wtMALT1 HSC2 cells (Kawamoto et al 2013). With respect to migration, a previous study demonstrated velocities of singlecell migration ( wtMALT1 HSC2 cells, 0.21 ± 0.01 µm/h; mock HSC2 cells, 1.01 ± 0.05 µm/h; Ohyama et al 2013).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The wtMALT1 HSC2 cells decelerated proliferation compared to mock HSC2 cells, and it was supported by the slow proliferation of endogenous MALT1-positive cells. This is consistent with cyclin D1 expression, which is almost terminated in wtMALT1 HSC2 cells (Kawamoto et al 2013). With respect to migration, a previous study demonstrated velocities of singlecell migration ( wtMALT1 HSC2 cells, 0.21 ± 0.01 µm/h; mock HSC2 cells, 1.01 ± 0.05 µm/h; Ohyama et al 2013).…”
Section: Discussionsupporting
confidence: 85%
“…Loss of MALT1 expression in oral carcinomas is associated with a worse patient prognosis (Chiba et al 2009) and stimulates proliferation and migration of carcinoma cells (Kawamoto et al 2013;Ohyama et al 2013). However, its involvement in carcinoma invasion, which is a prime determinant of the progression, is not defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study demonstrated that mucosa-associated lymphoid tissue 1 (MALT1) is expressed in the nucleus of oral epithelial cells (Chiba et al , 2009) and substitutes keratins depending on its expression (Kawamoto et al , 2013). The advanced carcinomas inactivate MALT1 expression by the promoter methylation, and the loss of expression worse the patient prognosis (Chiba et al , 2009).…”
mentioning
confidence: 99%
“…FABP4 transports LCFAs to the nucleus, which is required for stable binding with peroxisome-proliferator-activated receptor (PPAR)-γ. PPAR-γ expression in tongue carcinomas is higher in patients with an improved prognosis (42) and the administration of a PPAR-γ agonist inhibits the development of tongue carcinoma (43). However, oral carcinoma cells showing aggressive phenotypes in vitro strongly upregulate FABP4 expression (40,44). Detailed future studies are required in order to further clarify the role of ectopic expression.…”
Section: Discussionmentioning
confidence: 99%